Analysis of Velocity Uniformity in a Single Microchannel Plate with Rectangular Manifolds at Different Entrance Velocities. Issue 6 (8th May 2013) - Pan, M.; Shao, X.; Liang, L.; Hessel, Volker; Wang, Qi
Abstract The velocity distribution among microchannels with rectangular manifolds at different entrance velocities and the influences of structural parameters and entrance velocity on flow uniformity are investigated. The flow uniformity of a microchannel plate with rectangular manifold decreases with higher entrance velocity. At relatively low entrance velocity, the velocity distribution of the microchannel plate with centrosymmetric manifold is approximately symmetric. The velocity distribution becomes monotonically increased in a plate with large inlet manifold, whereas it becomes monotonically decreased in the one with large outlet manifold. A relatively uniform flow distribution can be obtained by the following conditions: longer microchannel, smaller microchannel width, symmetric manifold structure, larger manifold area, and perpendicular direction of inlet/outlet to the microchannel plane.